Synthesis of 1,1-Disubstituted Indenes via Palladium-Catalyzed Cross-Coupling of ortho-Alkenyl Bromobenzenes and α-Aryl-α-diazoesters - Feng, Xiao-Jiao; Fu, Jian-Guo; Zhao, Qian; Lu, Yu-Han; Zhang, Shu-Sheng; Feng, Chen-Guo (Synthesis, 2023)
Palladium-catalyzed cross-coupling of ortho-alkenyl bromobenzenes and α-aryl-α-diazoesters was realized. The reactions proceeded in moderate to excellent yields with broad substrate scope, providing a straightforward method for the synthesis of 1,1-disubstituted indenes. The reaction is thought to undergo a tandem alkenyl C–H activation/carbene insertion sequence, in which a C,C-pallada(II)cycle is the key intermediate.
Keywords: palladium catalyst; alkenyl C–H activation; carbene insertion; indene